Agile Kaizen Managing Continuous Improvement Far Beyond Retrospectives - Medinilla, Ángel; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Agile teams have been struggling with the concept of continuous improvement since the first Agile frameworks were developed, and still very little has been written about the practice of continuous improvement in Agile environments. Although team retrospectives have been prescribed and some practices have been introduced in order to implement and facilitate them, the truth is that most Agile teams are conducting dull retrospectives that end with a list of things that have been done wrong, just to repeat the same list two weeks later at the next meeting. Instead of listing hundreds of Japanese-labeled tools, this book gives you practical insights into how to spot improvement opportunities, how to plan for improvement and how to engage everyone in your company in the Kaizen process. In addition, it will also provide you with 27 proven practices and 12 bonus activities to introduce into your retrospectives in order to keep them fresh, creative and exciting, so you can promise a team that, in a year’s time, no two retrospectives will be alike. This book helps you as a manager, team leader, change agent or consultant in any type of organization to unleash the real power of Kaizen cultures – no matter what kind of organization, market, product, technology, vision, goal or size. It provides you with the background, tools and practical hints on how to engage your organization in a process of continuous quest for new and better ways of performing.
Part I – Agile Kaizen -- Understanding Kaizen -- Why and How Kaizen Fails -- Retrospectives and Kaizen Events -- Team Kaizen -- Process Kaizen -- Product Kaizen -- Epilogue: Implementing the Framework for Agile Kaizen -- PART II – Retrospective Activities And Games -- Process Activities -- Product Activities.
Keywords: Management information systems; Computer science; Project management; Management; Software engineering; Management of Computing and Information Systems; Project Management; Management; Software Engineering; Software Management